Prevalence, species composition, and associated risk factors of small ruminant gastrointestinal nematodes in South Omo zone, South-western Ethiopia - Tesfaye, Tegegn (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: This study was conducted to generate data on the prevalence, species composition, and factors associated with small ruminant nematode infection in the South Omo zone, in South-western Ethiopia. Material and Methods: A cross-sectional study through fecal nematode parasite examination was conducted. Simple floatation test and coproculture, followed by Baermann technique, were used for nematode egg and third-stage larvae (L3) separation and identification. The McMaster method was used to calculate the egg per gram of feces (EPG). Results: From a total of 242 sheep and goats examined, 72.34% were infested with single or mixed nematode parasites. District, “Kebele”, species, body condition score, and age were significantly (p < 0.05) associated with nematode infestation. Simple logistic regression analysis indicated that nematode infestation in Bena-Tsemay district (78.33%) was significantly (p < 0.05) higher by a factor of 0.54 (OR 95% CI: 0.30–0.96) than Hamer district (66.39%). Among the species, caprine (79.43%) was significantly (p < 0.05) infested than ovine (62.37%) by a factor of 0.45 (OR 95% CI: 0.25–0.81). Moreover, infestation on poor (79.12%) and medium (70.96%) body conditioned animals was higher by a factor of 2.94 (OR 95% CI: 1.41–6.26) and 1.76 (OR 95% CI: 0.88–3.53) than on good body conditioned animals (63.79%). Likewise, infestation in age groups of 1–3 years (78.66%) and >3 years (84.40%) was significantly (p < 0.05) higher by a factor of 4.83 (OR 95% CI: 2.31–10.46) and 8.23 (OR 95% CI: 3.98–17.75) than younger age groups (41.37%), respectively. A moderate parasitic burden was observed on 52.90% of gastrointestinal nematodes (GIN)-infested animals with significantly (p < 0.05) higher EPG in females than males. Furthermore, mixed infestation of Trichostrongylus axei and Eimeria (6.19%), Haemonchus contortus and Eimeria (5.78%), and Trichostrongylus vitrines and Eimeria (5.78%) were dominantly identified. On the contrary, T. axei (15.70%), Eimeria (8.67%), H. contortus (7.43%), and Trichostrongylus colubriformis (7.02%) were dominant single infestations. Conclusion: The current study revealed the highest prevalence of GIN in the study area, which needs strategic control, needs to enhance community awareness toward GIN control and prevention, and to implement further investigation into anthelminthic efficacy to solve the problem. J. Adv. Vet. Anim. Res., 8(4): 597-605, December 2021 http://doi.org/10.5455/javar.2021.h550